First record of the family Sialidae (Megaloptera) from Thailand and description of the female and putative larva of Indosialis bannaensis - Bowles, David E.; Contreras-Ramos, Atilano (Zootaxa, 2016)
Indosialis bannaensis is reported from northern Thailand marking the first record of the family, genus, and species from this country. The female and the probable larva of the species are described for the first time.